2021
DOI: 10.1021/acsagscitech.1c00243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Factors Affecting In Planta Gene Editing Efficiency in Wheat (Triticum aestivum L.)

Abstract: Gene editing in polyploid crops still suffers from low efficiency, and further improvement is needed for its routine implementation in the modern breeding practice. Here we examined factors that affect the CRISPR/Cas9-mediated gene editing efficiency in allohexaploid wheat plants. We selected three guide RNAs (gRNAs) and evaluated the potential of using heat shock at the seedlings stage to increase editing efficiency in transgenic plants. Only one out of three gRNAs demonstrated significantly increased editing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The gRNA#10 seeding sequence targeting three sub-genomic copies of TaGW2 was cloned into the JD633 plasmid carrying GRF–GIF and Cas9/gRNA expression cassettes. The CAPS assay for three sub-genomes targeted by gRNA#10 was performed as described previously ( Xu et al, 2022 ) using Sma I restriction digestion. PC-D, digested WT control (cv.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The gRNA#10 seeding sequence targeting three sub-genomic copies of TaGW2 was cloned into the JD633 plasmid carrying GRF–GIF and Cas9/gRNA expression cassettes. The CAPS assay for three sub-genomes targeted by gRNA#10 was performed as described previously ( Xu et al, 2022 ) using Sma I restriction digestion. PC-D, digested WT control (cv.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, others and we have demonstrated that biolisticmediated transformation can effectively generate edited wheat plants (Li et al, 2021;Xu et al, 2022). Here, we tested the efficiency of GE with the single-guide RNA (gRNA#10) targeting six copies of the wheat grain width and weight2 gene (TaGW2) (Wang et al, 2018).…”
Section: Agrobacterium-mediated Wheat Transformation Results In the E...mentioning
confidence: 99%
See 2 more Smart Citations
“…The work by Xu et al 7 addresses the low genome-editing efficiency in polyploid crops. By examining factors that affect the CRISPR/Cas9-mediated gene editing efficiency in allohexaploid wheat plants, the authors found that heat shock treatment could significantly increase editing efficiency.…”
mentioning
confidence: 99%